The Impact of Urban Public Spaces Design on Children's Engagement in Social and Interactive Activities - Duhair, Amir (Journal of Architecture and environment of child, 2024)
With the spread of urbanization, cities around the world have been affected by a large and rapid increase in population, which has put pressure on their resources and infrastructure. This negatively affected the space allocated for public spaces such as squares, gardens and play areas for the benefit of the residential barn, which made the places designated for children within the city shrink unevenly. As a result, the design of these places plays a major role in achieving their important role related to the child, providing the necessary spaces in addition to effective design can reflect positively on the child's development within the city. This study seeks to research the impact of urban public space design on children's participation in social and interactive activities, as this theoretical study tries to review previous literature and studies and highlight the most prominent of them to identify the factors that must be taken into account in the design of urban public spaces, and to provide aspects that must be studied in the future to bridge the gaps between theoretical studies and applied research within the urban environment